Transient aerodynamic pressures and forces on trackside and overhead structures due to passing trains. Part 1: Model-scale experiments; Part 2: Standards applications. (January 2014) - Baker, Christopher; Jordan, Sarah; Gilbert, Timothy; Quinn, Andrew; Sterling, Mark; Johnson, Terry; Lane, John
This is the first part of a two-part paper that describes the results of an experimental investigation to measure the aerodynamic pressure forces on structures in the vicinity of railway tracks. The investigations were carried out in order to obtain a fundamental understanding of the nature of the phenomenon and to obtain data for a variety of railway infrastructure geometries of particular relevance to the UK situation, in order to provide material for a National Annex to the relevant Eurocode. The experiments were carried out on the moving model TRAIN Rig, with models of three different sorts of trains with different nose types, and a variety of infrastructures types: vertical hoardings, overbridges, station canopies and trestle platforms. The transient loads that were measured had a characteristic form: a positive pressure peak followed by a negative pressure peak. In general the magnitudes of the two peaks were different, and varied with infrastructure type and position, as well as with train type. As would be expected, the more streamlined the train, the lower were the magnitudes of the pressure transients. A comparison of the experimental results was made with a variety of existing model- scale and full-scale data and a broad consistency was demonstrated, within the limits that the rather different experimental conditions in the various cases would allow. An analysis of the scaling of these pressure transients was carried out, and it was shown that whilst there was a reasonable coalescence around a theoretical formulation, the complexity of the flows involved meant that a general scaling formulation could not be achieved. Part 2 of this paper will consider the application of the results to the development of revised standards formulations.